Olecranon With Concomitant Radial Head Fracture: A Case Series of Fifteen Patients - Ditsios, Konstantinos; Pitsilos, Charalampos; Katsimentzas, Triantafyllos; Konstantinou, Panagiotis; Christidis, Panagiotis; Papadopoulos, Pericles (Frontiers in Surgery, 2022)
Introduction: Simultaneous olecranon and radial head fractures are rare injuries and due to this factor, the outcome of the selected therapy is not widely studied. The aim of this study is to report and evaluate the functional outcome of surgical treatment of olecranon and simultaneous radial head fractures. Material and Methods: This is a retrospective study of fifteen patients with olecranon and concomitant radial head fractures presenting to our orthopaedic department between 2015 and 2020. Olecranon fractures were classified by Mayo classification and radial head fractures by Mason classification and were managed appropriately. Main outcome measurements include range of elbow extension-flexion, pronation-supination, Broberg and Morrey rating system score and quickDASH score. Results: Our study included 6 females and 9 males with a mean age of 50 (r, 25-73). Mean follow-up was 31 months (r, 3-51). Olecranon fractures were fixed with tension band with K-Wires or intramedullary compression screw or locking plate. Radial head fractures were fixed with headless compression screws or mini plate or replaced (radial head arthroplasty). Postoperative outcome was an average 115ο extension-flexion arc and 135ο pronation-supination arc. The mean Broberg and Morrey rating system score was 78 and the mean quickDASH score was 25, indicating a good result. Two cases of heterotopic ossification were present and no nonunion was noted. Conclusion: Surgical management of combined olecranon and radial head fractures with correct technique can result in restoration of a functional movement arc and a satisfactory outcome.